IMPLEMENTASI OPERATIONAL AMPLIFIER PADA TAPIS AUDIO AKTIF TOPOLOGY SALLENKEY TIGA KANAL PADA PENGUAT AUDIO - Putri Nofi Liana Nugroho; Ibrahim Nawawi; Dwi Novianto (Universitas Negeri Surabaya, 2026)
The roll off on the 2nd order active filteris still too large around -40 dB/decade so that a 4th order active filteris needed so that the roll off becomes sharper, which is close to -80 dB/decade. This study aims to design a 4th order active filterand implement it in real life on a 3-way active speaker. The active filters designed are Active low pass filter, Active Band Pass filterand Active High Pass filterof order 4 with Sallenkey topology. The 4th order active filtercircuit is made by cascading the 2nd order active filtercircuit of Sallenkey topology. The active filterresponse measurement is carried out using a soundcard and frequency response analysis using smartlive software. Comparing the roll off of the active filterin theory, simulation and implementation on a 3-way active speaker. The roll off results in the simulation using Octave software are that the LPF produces a roll off of -76.99 dB/decade, the BPF of the HPF section produces a roll off of -76.6 dB/decade and the BPF of the LPF section produces a roll off of -77.83 dB/decade, the HPF produces a roll off of -77.06 dB/decade. While the roll off implementation on active speakers is that the LPF is -14.29 dB/decade, the BPF response of the HPF section produces a roll off of -40.14 dB/decade and the BPF of the LPF section produces a roll off of -44.78, while the HPF produces a roll off of -16.82 dB/decade.